Chomsky's School of Linguistics - Andarwati, Andarwati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2004)
Chomski linguistic flow presents theoretical concepts and views which is very meaningful in the formation of the paradigm of the nature and characteristics human language. Reasoning that underlies linguistic ideas, especially ranges the process of obtaining a second language or foreign language, including the concept of competence and performance, concepts of internal structures and surface structures, and structural concepts syntactic, provides a clear frame of mind about the position of understanding flow this linguistics in looking at human language. The issue that was born give a meaningful contribution to linguistic development don’t the implication in teaching second language or foreign language.